STREPTOMYCIN FORMATION BY INTACT MYCELIUM OF STREPTOMYCES GRISEUS - Nomi, Ryosaku (1963)
Nomi, Ryosaku (Rutgers, The State University, New Brunswick, N.J.). Streptomycin formation by intact mycelium of Streptomyces griseus. J. Bacteriol. 86:1220–1230. 1963.—A study was made of streptomycin formation by intact mycelium of Streptomyces griseus 107 grown in glucose-yeast extract medium. When mycelium harvested after 24, 48, and 72 hr was compared, the earliest growth showed the highest activity in producing streptomycin from glucose. The concentration of streptomycin in the mycelium was higher in the older growth. Calcium chloride had a remarkable effect in increasing streptomycin production from the precursors in the mycelium, especially when the mycelium was grown for 48 hr or longer. The effect of calcium chloride cannot be attributed to the precipitation of an excess of inorganic phosphate in the medium. Glucose, fructose, glycerol, lactic acid, glucosamine, streptidine, and inositol stimulated streptomycin formation, whereas gluconic acid, glucuronic acid, streptamine, and strepturea did not. When 24-hr-old mycelium was suspended and shaken in 0.5% glucose solution, the antibiotic precursors necessary to produce streptomycin were found mainly in the supernatant of the culture rather than in the mycelium. The supernatant included some substance which had a weak antibiotic activity. This substance was less basic than streptomycin and was transformed to streptomycin with a remarkable increase in antibiotic activity.